Radiofrequency Catheter Ablation of Atrioventricular Nodal Reentrant Tachycardia: It Is Not Always As It Is Expected - Arya, Arash (Indian Pacing and Electrophysiology Group, 2004)
Observation of Coincident arrhythmias is not uncommon but the co-existence of idiopathic verapamil sensitive left ventricular tachycardia (ILVT) with other arrhythmias is very rare. We hereby presented a 30 year old male patient with a history of frequent episodes of palpitations and sustained narrow complex tachycardia. During electrophysiologic study two arrhythmias, one with narrow complexes which was shown to be typical atrioventricular nodal re-entrant tachycardia and the other with wide QRS complexes and right bundle branch block and left axis morphology, compatible with ILVT, were inducible. Radiofrequency catheter ablation of both arrhythmias was done at two consecutive sessions. The patient has remained asymptomatic without antiarrhythmic therapy for the past six months.